Effects of feedstock characteristics on microwave-assisted pyrolysis – A review. (April 2017) - Zhang, Yaning; Chen, Paul; Liu, Shiyu; Peng, Peng; Min, Min; Cheng, Yanling; Anderson, Erik; Zhou, Nan; Fan, Liangliang; Liu, Chenghui; Chen, Guo; Liu, Yuhuan; et al.
Highlights: Effects of feedstock characteristics on microwave-assisted pyrolysis are reviewed. Feedstock particle size, moisture content, inorganics, and organics are covered. Heating dynamics, rate, options and bio-oil yield are discussed. Results of microwave-assisted and electrical heating pyrolysis are compared. Abstract: Microwave-assisted pyrolysis is an important approach to obtain bio-oil from biomass. Similar to conventional electrical heating pyrolysis, microwave-assisted pyrolysis is significantly affected by feedstock characteristics. However, microwave heating has its unique features which strongly depend on the physical and chemical properties of biomass feedstock. In this review, the relationships among heating, bio-oil yield, and feedstock particle size, moisture content, inorganics, and organics in microwave-assisted pyrolysis are discussed and compared with those in conventional electrical heating pyrolysis. The quantitative analysis of data reported in the literature showed a strong contrast between the conventional processes and microwave based processes. Microwave-assisted pyrolysis is a relatively new process with limited research compared with conventional electrical heating pyrolysis. The lack of understanding of some observed results warrant more and in-depth fundamental research.